TINGKAT STRES MAHASISWA PROFESI NERS STASE KOMUNITAS UNIVERSITAS MUHAMMADIYAH SEMARANG - Tri Nurhidayati (FIKkeS, 2014)
Clinical components are very important in the curriculum of nursing education. One of the barriers in learning is stress caused by many tasks, financial issues, exams, and lecturers. This study aimed to find out the level of distress among the students of nursing profession of Universitas Muhammadiyah Semarang and was to explore the experience of stress.This study used a descriptive. A questionnaire was administered to all 38 students the intern year in conjuction with the 28 item version of the general health questionnaire in first week and fourth week community stase. Semi-structured interviews were subsequently undertaken with two volunteers.Results of this study approximately 43,7% of respondents reported levels of severe stress. There were differences in distress between first week (4,41) and fourth week (7,27). That indicates elevating stress in fourth week.. It happened elevating stress in fourth week. It is recommended academic counselors, good support system and academic environment.Keywords: level of distress